Establishment of A Library to Improve the Quality of Human Resources in Apuai Village - Surti Surti; Gusti Marliani (Journal of Interdisciplinary Socio-Economic and Community Study, 2021)
Besides formal education such as schools and special training, education can also be obtained through libraries and other media such as the internet or television to access knowledge and information. Apuai Village, Aranio District, Banjar Regency is an underdeveloped village where people challenging to access the internet or telephone signals, and access roads to and from the village are not accessible. This condition is a significant obstacle to transferring information and knowledge from outside. To meet the community's needs in obtaining knowledge, the community service team took the initiative to establish the Apuai Village library. The hope is that the existence of this library can help the community, especially school children in the village, to have insight into creative thinking, cultivate spirituality, foster interest in reading, increase the efficiency and effectiveness of learning in the library. It is also hoped to increase entrepreneurship awareness for the readers for the local community with a low level of education. This community service activity also contains counseling to increase interest in reading. By diligently reading, people will find new knowledge to improve their ability to manage their natural and human potential. As a collection material, our library also provides books related to products and books on marketing strategies and product packaging to increase competitiveness. So far, the community can process natural products into something with better power. They also have difficulty in terms of packaging and marketing. It is because of the difficulty of access to information on attractive marketing and packaging techniques due to the problem of access to transportation, information, and telecommunications in this village.